PENINGKATAN KUALITAS DESTINASI EKOWISATA WAE BOBOK MELALUI PELATIHAN PENGEMBANGAN MEDIA INTERPRETASI - Ida Ayu Rostini; Roseven Rudiyanto; Septian Hutagalung; Fitri Ciptosari; Irna Karina J Kaban (Dharma: Jurnal Pengabdian Masyarakat, 2022)
Wae Bobok is a forest area in Tanjung Boleng Village, West Manggarai Regency, that used as a rest area for local people who drive between districts as well as an ecotourism destination. Not only a variety of special culinary, Wae Bobok offers a number of attractions in surrounding area, such as view point, spring, waterfall, outbond and camping site. Interpretive media is one aspect that needs to be developed in Wae Bobok in order to improve the quality of ecotourism destinations and increase knowledge for tourists. This community service activity aims to provide knowledge regarding the concept of interpretation and train the community in developing interpretation media in Wae Bobok area. By using a community based-development approach and field observations, this activity try to produce a short narrative of tourist attractions in Wae Bobok area as well as interpretive media such as brochure and promotional video that can be used by visitors.